Mongolia : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper aims to take stock of key challenges and propose recommendations on how to address them. Mongolia has taken important steps to address these challenges, but more should be done to tackle remaining gaps and ensure effective enforcement. Improving governance is a crucial step for Mongolia to achieve sustainable and inclusive growth. In order to substantially reduce corruption, a stronger anti-corruption framework should be accompanied by governance reforms across a range of state functions. On rule of law, the Worldwide Governance Indicators (WGI) place Mongolia above peers in Asia but below regional averages, indicating room for improvement. Although Mongolia has developed a legal framework since the transition to a market economy, observers point out that there are often loopholes and unintended consequences. Weak revenue administration can undermine fiscal sustainability while uneven enforcement of tax rules can damage the investment climate. State-owned enterprises would benefit from better governance, particularly given their central role in output and potential for creating fiscal liabilities.